NAL phase in K‐rich portions of the lower mantle. Issue 19 (8th October 2013) - Kato, Chie; Hirose, Kei; Komabayashi, Tetsuya; Ozawa, Haruka; Ohishi, Yasuo
Abstract [1] The stability of the K‐rich new aluminous (NAL) phase was examined on the join Na1.00Mg2.00Al4.80Si1.15O12‐K1.00Mg2.00Al4.80Si1.15O12 (Na100‐K100) up to 144 GPa by X‐ray diffraction in a laser‐heated diamond anvil cell. Single‐phase K100 and Na50K50 NAL were formed up to the lower mantle conditions, and the NAL phase coexisted with the calcium ferrite–type (CF) phase at 120 GPa and 2300 K for the Na75K25 bulk composition. This is a striking contrast to the K‐free (Na100) NAL that becomes unstable above 27 GPa at 1850 K, which suggests that potassium stabilizes NAL at significantly higher pressures. K‐rich NAL may host potassium in the lower mantle that contains K2O more than 0.09 wt %. In addition, the NAL phase likely formed owing to partial melting in the ultralow‐velocity zone or because of a basal magma ocean. Future seismological observations may clarify whether NAL is a radiogenic heat source above the core‐mantle boundary.